Changes in PGC‐1α/SIRT1 Signaling Impact on Mitochondrial Homeostasis in Amyloid-Beta Peptide Toxicity Model - Panes, Jessica D.; Godoy, Pamela A.; Silva-Grecchi, Tiare; Celis, María T.; Ramirez-Molina, Oscar; Gavilan, Javiera; Muñoz-Montecino, Carola; Castro, Patricio A.; Moraga-Cid, Gustavo; Yévenes, Gonzalo E.; Guzmán, Leonardo; Salisbury, Jeffrey L.; et al. (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive impairment that increasingly afflicts the elderly population. Soluble oligomers (AβOs) has been implicated in AD pathogenesis: however, the molecular events underlying a role for Aβ are not well understood. We studied the effects of AβOs on mitochondrial function and on key proteins that regulate mitochondrial dynamics and biogenesis in hippocampal neurons and PC-12 cells. We find that AβOs treatment caused a reduction in total Mfn1 after a 2h exposure (42±11%); while DRP1 increased at 1h and 2h (205±22% and 198±27%, respectively), correlating to changes in mitochondrial morphology. We also observed that SIRT1 levels were reduced after acute and chronic AβOs treatment (68±7% and 77±6%, respectively); while PGC-1α levels were reduced with the same time treatments (68±8% and 67±7%, respectively). Interestingly, we found that chronic treatment with AβOs increased the levels of pSIRT1 (24h: 157±18%), and we observed changes in the PGC-1α and p-SIRT1 nucleus/cytosol ratio and SIRT1-PGC-1α interaction pattern after chronic exposure to AβOs. Our data suggest that AβOs induce important changes in the level and localization of mitochondrial proteins related with the loss of mitochondrial function that are mediated by a fast and sustained SIRT1/PGC-1α complex disruption promoting a “non-return point” to an irreversible synaptic failure and neuronal network disconnection.